OPPORTUNITIES TO USE "GREEN BRAND" MARKETING STRATEGIES IN THE FASHION BUSINESS (Marketing Journal, 2025)
This article explores the potential of applying “green brand” marketing strategies in Uzbekistanʼs fashion industry. It analyzes how ecological innovations in sewing and knitwear enterprises influence consumer behavior. The study finds that green innovatio ns enhance brand image and encourage conscious purchasing decisions. Practical recommendations are proposed based on the findings.
Keywords: marketing; fashion; green brand; digital marketing; marketing strategy; green innovations